Intervensi Media Audiovisual Animatif terhadap Sikap Permisif Remaja terkait Risiko Kesehatan Rokok Elektrik : Studi Pra-Eksperimental - Ni Komang Ayu Evi Mahayani; Ni Kadek Yuni Lestari; Ni Luh Putu Dewi Puspawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The use of electronic cigarettes among adolescents continues to increase, while socialization regarding their dangers in schools remains limited. Many adolescents have a permissive attitude toward e-cigarettes and consider them safer than conventional cigarettes. The lack of health education and the influence of social media strengthen positive perceptions of e-cigarette use. This study aims to determine the effect of educational video animation on adolescents’ attitudes toward the health impacts of e-cigarette use. This research employed a quantitative pre-experimental design with a One Group Pre-test Post-test Design. The sample consisted of 92 respondents selected using a proportional stratified random sampling technique. The intervention was conducted once using an educational animated video. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that before the intervention, 18 respondents (20%) had negative attitudes and 74 respondents (80%) had positive attitudes, while after the intervention, all respondents (100%) demonstrated positive attitudes. The bivariate analysis obtained a p value = 0.000 (p < 0.05), indicating a significant effect of educational animated videos on adolescents’ attitudes toward the health impacts of e-cigarette use. Animated video media proved effective in enhancing understanding and shaping positive attitudes among adolescents as it can attract attention, clarify messages, and evoke stronger emotional impressions compared to conventional media.